Meeting Report for the 39th Annual Meeting and Workshops of the Society of Cardiovascular Anesthesiologists. (February 2018) - Fox, Amanda A.; Eaton, Michael P.; Shillcutt, Sasha K.
Abstract : Published ahead of print December 11, 2017.